An outcomes evaluation of the Zim-TTECH cervical cancer intervention in Harare Metropolitan Province, Zimbabwe - Tapera, Oscar (Institute for Monitoring and Evaluation, 2023)
This report presents the findings of an outcomes evaluation of the Zimbabwe Technical Assistance, Training and Education for Health's (Zim-TTECH) cervical cancer intervention in Harare and Epworth districts (Harare Metropolitan province). This programme seeks to improve access and uptake of cervical cancer screening and treatment among women living with HIV through recruitment, training and mentorship of nurses, procurement of equipment and commodities, providing support for diagnosis and referral for treatment services, and quality assessment of cervical cancer services. The evaluation interrogated the plausibility of the programme theory of the Zim-TTECH intervention and assessed its short- and medium outcomes. Methods The evaluation used a mixed-methods approach with both qualitative and quantitative data collection methods. This comprised a desk review of programme documents and relevant literature, secondary analysis of programme routine data and collection of primary data. Quantative descriptive analysis was conducted to determine coverage (in percentage) of Zim-TTECH cervical cancer services between 2019- 2021. Qualitative analysis was used to complement quantitative data and aid in the interpretation of programme results. Key Results This assessment showed that the Zim-TTECH cervical cancer intervention contributed to the increase in awareness among women living with HIV and health workers. The programme capacitated health workers to conduct effective health education and awareness-raising campaigns for cervical cancer. The evaluation revealed that the Zim-TTECH cervical cancer intervention improved access to cervical cancer services among women living with HIV. Additionally, the intervention did not deny women who were HIV-negative services though the reach for this group is not routinely documented and reported. Results from the evaluation showed that LEEP was the main treatment type used in Harare and Epworth followed by cryotherapy and thermablation techniques. This assessment also showed that the Zim-TTECH cervical cancer intervention contributed positively to the following areas: increasing access to cervical cancer services, early detection of pre-cancers and invasive disease and increased health education and awareness of cervical cancer among women and health workers. The evaluation also revealed some negative implications of the Zim-TTECH intervention on the health system which include the following: the programme‘s screening resulted in the detection of invasive cervical cancer cases which were referred to weak and ill-capacitated public health facilities, and most screening services are offered in HIV clinics which results in some women who are not HIV positive not wanting to screen for fear of stigma and the programme also contributed to staff attrition in public health facilities as they search for better opportunities in the NGO sector and outside the country. The Zim-TTECH cervical cancer programme rapidly adjusted to the new COVID-19 protocols in 2020 to ensure continuity of services though the demand side was affected by protracted lockdowns. The programme has also been keeping in tandem with technological evolutions including the adoption of thermoablative techniques and planning for the rolling out of highly sensitive human papilloma virus (HPV) DNA testing in line with Ministry of Health strategies and WHO guidelines. However, discussions are still ongoing on the adoption of HPV screening as the primary method as it will negate the ‘see and treat' approach. This evaluation showed that cervical cancer services were likely to continue in Harare and Epworth after the cessation of Zim-TTECH support albeit at a lower scale. The Zim-TTECH intervention is based in public health facilities that have been offering cervical cancer services even before partner support came through and these are likely to continue in their absence. Conclusions Findings from this evaluation showed that Zim-TTECH cervical cancer intervention was relatively effective with regards to short-medium term outcomes, although the COVID-19 pandemic saw disruptions of cervical cancer services which affected service delivery/uptake in 2020-2021. However, the key shortfalls of the intervention revealed in this evaluation showed systemic/structural gaps with the design of health interventions in the country as well as the vertical approaches which are also being perpetuated by donors. Additionally, given the huge resource shortfalls in the MoHCC due to protracted underfunding, there is evidence of limited coordination/leadership capacities to guide partners who come up with piecemeal interventions. Despite the revealed shortcomings of the intervention there are opportunities to improve services including treatment of invasive cervical cancer. Overall, better partnerships and coordination among government, NGOs and donors will be a game changer in ensuring continuity of services for cervical cancer in low-resource settings.